THE ELABORATION OF SUFISM VALUE AND PSYCHOLOGY TO IMPROVE MENTAL HEALTH IN FACING PANDEMICS - Saifuddin, Ahmad (Psikis : Jurnal Psikologi Islami, 2022)
Indonesia is one of the countries affected by Covid-19 virus. These impacts influence both physical and psychological health. This study aimed to conceptualize the elaboration of Sufism values with psychology to deal with Covid-19. The research was conducted with a literature review. This research showed that many values of Sufism play an essential role in dealing with Covid-19, for example seclusion is the essence of physical distancing to prevent individuals from worrying; zuhud, qana'ah, and tawakal attitudes prevent individuals from stress; meditative dhikr helps individuals turn irrational thoughts into rational ones; and imitating Sufism as a social movement can create an impact on the society so that they can face Covid-19 together. Thus, this study found that Sufism has a down-to-earth role, namely improving the mental health of individuals during the Covid-19 pandemic.